Podjetniška aktivnost, aspiracije in odnos do podjetništva: GEM Slovenija 2010 - Rebernik, Miroslav; Tominc, Polona; Crnogaj, Katja (University of Maribor Press, 2011)
Entrepreneurial Activity, Aspirations and Attitude towards Entrepreneurship : GEM Slovenia 2010. Despite the fact that the role and influence of various types of entrepreneurship differ according to different developmental stages of economy and society, entrepreneurship remains important, because it ensures development. The study of entrepreneurship thus involves mainly the study of its fundamental driving force, i.e. entrepreneurs and their ambitions, innovativeness and entrepreneurship skills, as well as their fears and the reasons that prevent skilled individuals from embarking on entrepreneurship activities. The Global Entrepreneurship Monitor (GEM), which has studied entrepreneurship globally since 1999, emphasises the role of individuals and builds its scientific evidence on information gathered from extensive questionnaires these individuals fill in. They live and work in different economic, social, cultural and political environments, which has an important impact on their intentions and actions, which our research activities try to identify and understand. In addition to general requirements, which foster or promote entrepreneurship in individual countries, the GEM focuses on three issues, namely the attitude towards entrepreneurship, engagement in entrepreneurship activities and entrepreneurship aspirations. In 2010, Slovenia was compared with 58 countries from around the world.